Línea Sur 6 : foreign policy journal sep/dec 2013 - Ministerio de Relaciones Exteriores y Movilidad Humana (Quito, Ecuador : Ministerio de Relaciones Exteriores, 2013)
With this sexth editon of Línea Sur, the Foreign Policy Journal, entitled" Security and Human Rights, " we are surely movin forward with the circulaations and implemtación of an alternative contribution to the debate on contemporaty global issues.
Contenido Message from the minister of foreign affairs Dossier Presentation of the Dossier The challenge of politics in a multipolar world Asylum as an instrument for the defense of human rights Electronic espionage: implications for the protection of sovereignty and human rights South american integration perspectives on defense and security and defense Strategic agenda and integration Policies to care for people with disabilites in Ecuador: toward an "Export Model" Twenty-first century socialism in Bolivia : The gender agenda Current affairs The incidente of Evo Morales presential. Airline: A matter of intenational rights, state security, human rights, and national dignity Manipulating internatinal security and human rights as geopolitical tools: doublespeak in the cases of Egypt and Syria Interview The role of contemporary whistleblowers and national security in relation to human irghts, from the perspective of Julian Assange Historial archives of the Minist of foreign affarirs State and nationalist revolution in latin america Foreign affaairs timeline
La Revista línea sur 6, se trabajó por analítica
Incluye referencias
Keywords: POLÍTICA EXTERIOR -- AMÉRICA LATINA -- PUBLICACIONES SERIADAS; ASUNTOS EXTERIORES -- AMÉRICA LATINA -- PUBLICACIONES SERIADAS